Traumatic Brain Injury in Alpine Winter Sports: Comparison of Two Case Series from a Swiss Trauma Center 30 Years Apart - Kiss-Bodolay, Daniel; Papadimitriou, Kyriakos; Simonin, Alexandre; Huscher, Karen; Fournier, Jean-Yves (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2023)
Background Between 3 and 15% of winter sports–related injuries are related to head injuries, which are the primary cause of mortality and disability among skiers. Despite the widespread adoption of helmets in winter sports, which has reduced the incidence of direct head injury, there is a paradoxical trend of an increasing number of individuals wearing helmets sustaining diffuse axonal injuries (DAI), which can result in severe neurologic sequelae.Methods We retrospectively reviewed 100 cases collected by the senior author of this work from 13 full winter seasons during the period from 1981 to 1993 and compared them with 17 patients admitted during the more shortened 2019 to 2020 ski season due to COVID-19. All data analyzed come from a single institution. Population characteristics, mechanism of injury, helmet use, need for surgical treatment, diagnosis, and outcome were collected. Descriptive statistics were used to compare the two databases.Results From February 1981 to January 2020, most skiers with head injuries were men (76% for the 1981–1993 and 85% for 2020). The proportion of patients aged over 50 increased from <20% in 1981 to 65% in 2020 (p < 0.01), with a median age of 60 years (range: 22–83 years). Low- to medium-velocity injuries were identified in 76% (13) of cases during the 2019 to 2020 season against 38% (28/74) during the 1981 to 1993 seasons (p < 0.01). All injured patients during the 2020 season wore a helmet, whereas none of the patients between 1981 and 1993 wore one (p < 0.01). DAI was observed in six cases (35%) for the 2019 to 2020 season against nine cases (9%) for the 1981 to 1993 season (p < 0.01). Thirty-four percent (34) of patients during the 1981 to 1993 seasons and 18% (3) of patients during the 2019 to 2020 season suffered skeletal fractures (p = 0.02). Among the 100 patients of the 1981 to 1993 seasons, 13 (13%) died against 1 (6%) from the recent season during care at the hospital (p = 0.15). Neurosurgical intervention was performed in 30 (30%) and 2 (12%) patients for the 1981 to 1993 and 2019 to 2020 seasons, respectively (p = 0.003). Neuropsychological sequelae were reported in 17% (7/42) of patients from the 1981 to 1993 seasons and cognitive evaluation before discharge detected significant impairments in 24% (4/17) of the patients from the 2019 to 2020 season (p = 0.29).Conclusion Helmet use among skiers sustaining head trauma has increased from none in the period from 1981 to 1993 to 100% during the 2019 to 2020 season, resulting in a reduction in the number of skull fractures and deaths. However, our observations suggest a marked shift in the type of intracranial injuries sustained, including a rise in the number of skiers experiencing DAI, sometimes with severe neurologic outcomes. The reasons for this paradoxical trend can only be speculated upon, leading to the question of whether the perceived benefits of helmet use in winter sports are actually misinterpreted.
Keywords: traumatic brain injury; diffuse axonal injury; winter sports; Swiss trauma center; helmet